Restorative justice: promoting peace and wellbeing - Velez, Gabriel; Gavrielides, Theo (Peace psychology book series, 2022)
Section 1: Intrapersonal Peace -- Chapter 1: Developing Peaceful Self-Identities Through Restorative Practices -- Chapter 2: Restorative Practices as Peace Pedagogy -- Chapter 3: Promoting Coping and Resilience Through Reparation -- Section 2: Interpersonal, Intergroup, and Intercommunity Peace -- Chapter 4: Bridging the Unbridgeable Divides -- Chapter 5: Preventing and Healing Community Violence -- Chapter 6: Addressing Systemic Injustice and Oppression -- Chapter 7: Peace and Harmony in Post-Conflict Societies -- Chapter 8: Restoring from Non-Western Lenses -- Chapter 9: Bridging Racial/Ethnic Divides -- Section 3: Institutional, International and Non-state Actors -- Chapter 9: Changing School Cultures -- Chapter 10: Reshaping Discipline: Ending Inequities of Retributive Measures in Schools -- Chapter 11: Forgiving and Repairing: Restorative Justice and the Criminal Justice System -- Chapter 12: Former Combatants and Reintegration -- Chapter 13: Reparations and Addressing State Atrocities.